If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-10)=-33+4x+1
We move all terms to the left:
3(2x-10)-(-33+4x+1)=0
We add all the numbers together, and all the variables
3(2x-10)-(4x-32)=0
We multiply parentheses
6x-(4x-32)-30=0
We get rid of parentheses
6x-4x+32-30=0
We add all the numbers together, and all the variables
2x+2=0
We move all terms containing x to the left, all other terms to the right
2x=-2
x=-2/2
x=-1
| 3y+36=-3y | | ⅗y=6+7y | | 4-4x=-8x-8 | | -1-7(6r+3)=190 | | 9p-98=-9p+-8 | | -8x=2x-4 | | -8×=3x-4 | | 6t+27=t+32 | | 15x-7+7x-3+12x-14=180 | | x.53=22+x* | | 4(10-x)=-(x-1) | | 2s+16=-4s-6 | | 2=2(x-1)+10 | | 3c+-20c=-17 | | -44=4(x-5) | | 4.5x-11=-2 | | -4t+-16t-(-9t)+2t-(-13t)=-16 | | 5x+3x=x+11 | | 30=6(j+1) | | 10(q+1)=90 | | k-34/5=8 | | -4(-2x+8)=-6(1x-18)+12x | | 4(x+5)=Ax+ | | 88=5t+13 | | 3y-48=84 | | 4-18-x=14 | | 6+6y=6+6y= −30−30 | | 8w-6w+3w+2w=14 | | -4(-2+8)=-6(x-18)+12x | | -5z+8-3z=48 | | 17k-8k-3k-5k=19 | | 18+x=-(x+3) |